Urgensi Kontruksi Fungsi Kepemimpinan Kristen Menuju Visi Organisasi Gereja - setiabudi, Hengki irawan; Bindargo; Sanger, Christina (Sekolah Tinggi Teologi Pelita Hati, 2025)
Every organization cannot be separated from the word leadership, namely the person who leads the organization, especially the church, towards the vision that has been set. Church leadership as an organization obviously has many situations where the church does not run according to the expected vision. Bad situations arise such as: the organization stagnates and even regresses, or even the organization has complex problems such as internal conflicts, divisions, services not going well, low motivation to serve, and so on. The purpose of this research is to identify and analyze the functions of leadership, especially in the church, whether it is running or not. The functions described will be used as a barometer of leadership performance. The methodology used by the researchers is a qualitative method of literacy studies and observations to several churches experiencing problems of decline and stagnation. The researcher's hypothesis is how leaders perform leadership functions in running a church organization. By exercising leadership functions such as: influence, change, transformation, motivation, and vision, it is hoped that the organization can operate according to agreed upon expectations. The important thing is how leaders rebuild their leadership functions.